Comparison between the physiological response to roller skiing and in-line skating in biathletes - Baum, K.; Hoy, S.; Fischer, F.; Leyk, D.; Schmidt, O.; Eßfeld, D. (Medicine & Science in Sports & Exercise, 1999)
The results show that in-line skating can be regarded as an alternative to roller skiing for off-seasonal training in nordic disciplines. A potential advantage of in-line skating is that aerobic training intensities can be obtained at competitive velocities.